There's Sand in My Infinity Pool: Land Reclamation and the Rewriting of Singapore. Issue 2 (3rd July 2017) - Jamieson, William
Abstract : "There's Sand in My Infinity Pool" explores land reclamation in Singapore as a speculative material and cultural practice. Typically presented as either a practical engineering feat or an ecologically disastrous approach to coastal development, the significance of land reclamation in the cultural formation of identity and landscape has yet to be addressed. Given the ongoing and speculative nature of land reclamation, this practice-led research seeks to position land reclamation as a form of writing to identify the rewritten boundaries of memory and identity, unearthing the unacknowledged implications of land reclamation as a material and cultural practice in the formation of national identity. Sourced from interviews, ethnographic accounts, and autoethnography, the narratives examine what it means to live with and through land reclamation. The "breakwater" widens the field of conceptual enquiry, juxtaposing ideas from human geography, literary criticism, and critical theory to widen the framework for interrogating this practice of nation building.